Design method of human–industrial robot collaborative workstation with industrial application. Issue 9 (1st September 2020) - Ore, Fredrik; Jiménez Sánchez, Juan Luis; Wiktorsson, Magnus; Hanson, Lars
ABSTRACT: How to design Human–Industrial Robot Collaborative (HIRC) workstations is one of the key challenges in the realisation of safe and efficient HIRC systems in industry. The aim of this paper is to present a simple method to be used in early phases of HIRC workstation design. The design method requires a simulation tool and is based on systematic design methodologies and its reference work, Pahl and Beitz´s engineering design framework. The proposed HIRC design method consists of four phases: planning and clarifying the work task, conceptual design, embodiment design and detail design, where iteration loops back to previous phases are vital. This design method is applied in an industrial HIRC design case on assembly of a flywheel cover on a heavy vehicle engine block. In this application example, a previously developed HIRC simulation software is used to generate quantitative values on identified evaluation criteria, in this case operation time and biomechanical load. This proposed HIRC design method in combination with any type of simulation tool enables the systematic design of HIRC workstations early in the production development process.